A decoupling process of Pakistan's agriculture sector: Insights from energy and economic perspectives. (15th January 2023) - Raza, Muhammad Yousaf; Wu, Rongxin; Lin, Boqiang
Abstract: As the energy-intensive and productive sector, agriculture enriched social prosperity, fed people, and enriched huge poverty worldwide. Development mechanisms, energy consumption and energy efficiency in the agriculture sector have become equally necessary in the services and industrial sectors. The study's main objective is to analyze the agricultural energy decomposition and its decoupling with the economic output in Pakistan from 1981 to 2020. For this, the study employed the logarithmic mean Divisia index method to give proof of the effect of four major driving factors, including agriculture energy intensity (AEI), agriculture economic output (AEO), agriculture labor intensity (ALI), and total agriculture land (TAL). The study gives a significant relationship between energy consumption and economic growth based on identified decoupling states. The outcomes show that AEO is the major factor in raising energy consumption. AEI and TAL show an increasing return to scale, while ALI shows mixed effects over the intervals. Only strong and expansive negative decoupling is maximally given in the analysis, while the other five decouplings show little impact. Thus, based on further policies, the strong negative decoupling state could be further substituted with strong decoupling using energy technologies. It suggests that the agriculture sector can attain mixed energy, energy management, enhance capital investment, and skilled labor because the speed of energy use is increasing. To check the provincial measures, costing, energy share, and carbon emission information can be further estimated. Highlights: Agricultural energy decomposition and decoupling with economic output are analyzed. LMDI method is used for four major driving factors using 1981–2020 statistics. Agriculture economic output is the major factor in raising energy consumption. Energy intensity and land show a rising trend, while labor shows mixed effects. This sector can reach mixed energy, management, enhance capital and skilled labor.